2016
DOI: 10.1136/jmedgenet-2016-104284
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 24 years national surveillance in different hereditary colorectal cancer subgroups leading to more individualised surveillance

Abstract: The risk of CRC in Lynch families is considerable, despite biannual surveillance. We suggest less frequent and more individualised surveillance in non-Lynch families. Individuals from families with a strong history of CRC could be offered 5-year surveillance colonoscopies (unless findings at the preceding surveillance session indicate shorter interval) and individuals from moderate-risk families could be handled with the population-based screening programme for CRC after an initial surveillance colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Moreover, given the lower risk of metachronous CRCs and longer interval between initial and metachronous CRCs in FCCTX, endoscopy can be performed less frequently and in a more individualized schedule. We suggest 5-year surveillance colonoscopies unless findings at the preceding surveillance session indicate the need for a shorter interval ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, given the lower risk of metachronous CRCs and longer interval between initial and metachronous CRCs in FCCTX, endoscopy can be performed less frequently and in a more individualized schedule. We suggest 5-year surveillance colonoscopies unless findings at the preceding surveillance session indicate the need for a shorter interval ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…While other cancers aside from CRC are also frequent in families with LS ( 16 , 17 ), extracolorectal cancers rarely occur in FCCTX families ( 6 , 8 ). An analysis of the long-term outcomes of different hereditary CRC subgroups concluded that less frequent but more individualized surveillance protocols would be beneficial for FCCTX cases ( 18 ). Nevertheless, these findings were derived from Western medical centers, and data in China remain lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Families have been included based on a suspicious family history of colorectal cancer, fulfilment of the Amsterdam I or II criteria [38], or identification of diseasepredisposing variants in genes linked to hereditary colorectal cancer. Based on family history, the register subclassifies families according to genotypic and phenotypic subsets [20]. The Danish HNPCC register identifies all family members in the Danish Civil Registration System, regardless of cancer history, based on data collected from clinical files and health care registers.…”
Section: Methodsmentioning
confidence: 99%
“…Families have been included based on a suspicious family history of colorectal cancer, fulfilment of the Amsterdam I or II criteria (Vasen et al, 2013), or identification of disease-predisposing variants in genes linked to hereditary colorectal cancer. Based on family history, the register subclassifies families according to genotypic and phenotypic subsets (Lindberg et al, 2017). The Danish HNPCC register identifies all family members in the Danish Civil Registration System, regardless of cancer history, based on data collected from clinical files and health care registers.…”
Section: Methodsmentioning
confidence: 99%